2015
DOI: 10.3109/0886022x.2015.1006083
|View full text |Cite
|
Sign up to set email alerts
|

Decrease of Urotensin II activity can impact on the volume status in predialysis chronic kidney disease

Abstract: Urotensin II (U-II) was thought to be one of the mediators of primary renal sodium retention due to effects on renal sodium excretion. For this purpose, the relationship between U-II and overhydration was investigated. A total of 107 patients were enrolled in the study. According to body compositor monitor analysis, fluid overload up to 1.1 L, was considered normohydration. Patients were divided according to hydration status; overhydrate (n ¼ 42) and normohydrate (n ¼ 65) were studied in both groups. Pulse wav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…However the authors noticed an increase in UII levels at the end of the HD session [ 36 ]. Furthermore, in a recent study, predialysis of UII levels were lower in overhydrated compared to normohydrated ESKD patients [ 37 ]. Taking into consideration previous reports on the relationship between low UII concentration and the risk of cardiovascular events in patients with CKD, the authors assume that low levels may be a therapeutic target in overhydrated CKD patients [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However the authors noticed an increase in UII levels at the end of the HD session [ 36 ]. Furthermore, in a recent study, predialysis of UII levels were lower in overhydrated compared to normohydrated ESKD patients [ 37 ]. Taking into consideration previous reports on the relationship between low UII concentration and the risk of cardiovascular events in patients with CKD, the authors assume that low levels may be a therapeutic target in overhydrated CKD patients [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is speculated, that the removal of fluids from our patients by HD and the resulting hemoconcentration may have a role in the increase of HDII levels after the completion of HD [ 36 , 37 ]. Moreover, UII is a middle size molecule (molecular mass = 1388.6 g/mol) and is only partially removed using the convential HD [ 36 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that UII promotes the proliferation of renal tubular epithelial cells (12), activates the epidermal growth factor receptor in rat renal tubular epithelial cells via the SHP-2 signaling pathway (13), inhibits renal tubular reabsorption of potassium and sodium (14), promotes intracellular calcium release (15) and inhibits apoptosis in NRK-52E rat proximal tubular epithelial cells (16). In addition, UII has been proposed as a target for treating patients with hypervolemic cardio-renal syndrome (17). UII exerts a potent vasoconstrictive action as well as renal profibrotic effects (18).…”
Section: Introductionmentioning
confidence: 99%